Science and scepticism: Drug information, young men and counterpublic health - Farrugia, A.; Fraser, Suzanne (Sage Publications, 2016)
It is perhaps no surprise that young people can be sceptical of the drug-related information they receive in school-based health education, health promotion and the media. Significant societal anxiety surrounds young people’s drug consumption, so it is tempting to approach this scepticism as a problem to be solved. In this article, we look closely at a group of young Australian men (n = 25), all of whom hold deeply sceptical views about the drug information they received in schools, social marketing campaigns and public speech generally. We do not approach their scepticism as a problem to be solved in itself, however. Instead, we analyse its origins and how it relates to the way knowledge is constructed in drug education, health promotion and media accounts of drug use. To conceptualise this scepticism, we draw on Irwin and Michael’s analysis of the changing relationship between science and society, Warner’s theorisation of publics and counterpublics, and Race’s related notion of ‘counterpublic health’. The article organises the data into three key themes: scepticism about the accuracy of the claims made about drug risks and dangers, scepticism about representations of drug users, and scepticism about the motivations behind the health messages and drug policy in general. We then draw these different aspects of scepticism together to argue that the young men can be seen to constitute a health ‘counterpublic’, and we consider the implications of this approach, arguing for what has been described as a more diplomatic engagement between science and publics.